Peran Kepemimpinan Visioner Berbasis Psikologi dalam Inovasi Pembelajaran dan Peningkatan Mutu Pendidikan - Mahmud (Khatulistiwa Insight: Islamic Education and Learning, 2025)
This study aims to analyze the role of visionary leadership based on psychological approaches in improving the quality of Islamic education at MAN 1 Situbondo. The focus of the study is directed toward how a leader applies psychological strategies in building the school's vision and culture to drive educational quality improvement. The research method used is a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. The results of the study show that the visionary leadership practiced by the head of the madrasah involves understanding the psychological characteristics of teachers and students, strengthening intrinsic motivation, and creating a supportive working environment. Empathetic communication strategies, personal empowerment, and continuous coaching have proven effective in building collective commitment toward a shared vision. The implications of implementing this leadership approach can be seen in improved teacher performance, increased student participation, and better academic achievement. These findings recommend the importance of integrating psychological aspects into the development of madrasah leadership capacity as a strategic effort to enhance the quality of Islamic education in the modern era.